Perspectives on corporate citizenship - Andriof, Jörg; McIntosh, Malcolm, 1953-2017 (Greenleaf Pub., 2001)
In today's society successful companies will increasingly be those that recognize that they have responsibilities to a range of stakeholders that go beyond compliance with the law. This book aims to help capture and distill emerging corporate trends in terms of content, context and processes.